Vacuum arc deposition of TiN, NbN and TiN/NbN multi-layer coatings - Travitzky, Nahum; et al. (Surface & Coatings Technology, 1999)
Single-layer coatings of TiN and NbN, and multi-layer coatings of TiN/NbN, were deposited onto WC-Co substrates using a triple-cathode vacuum arc plasma gun connected to a cylindrical plasma duct onto which an axial magnetic field was imposed. Additional magnetic fields were applied by two beam steering coils orientated normal to the duct axis. The magnetic field produced by the steering coils directed the plasma beam onto a substrate placed on the system axis, increasing the plasma flux to the sample. The single-layer coatings were produced by generating Ti or Nb plasmas in a nitrogen background at a pressure P in the range of 0.67 to 2.67Pa. Multi-layer coatings with 20, 50 and 100 layers were deposited by alternately switching the arcs on Ti and Nb cathodes. Coating structure and composition were studied by means of scanning electron microscopy (SEM) and X-ray diffraction (XRD). Microhardness and adhesion to the substrate were studied by Vickers' micro-indentation and scratch tests, respectively. It was shown that the phase composition of the NbN coatings depended on the deposition rate and P. The coatings deposited at low deposition rate (i.e. without the beam steering field) exhibited a single-phase cubic δ-NbN structure at P≥0.67Pa, whereas the coatings deposited with application of the beam steering field, at P=0.67 and 1.33Pa, were composed of a mixture of cubic δ-NbN and hexagonal NbN, while at P=2 and 2.67Pa, the hexagonal phase was not found. The phase composition of the TiN coatings was independent of the deposition rate and P in the range 0.67-2.67Pa. The highest microhardness (up to 38GPa) and scratch critical load (80-95N) were obtained for single-phase δ-NbN coatings deposited at P=0.67-1.33Pa and at low deposition rate. The microhardness of multi-layer TiN/NbN coatings of 3.2-3.6μm total thickness increased with increasing number of alternating layers, but did not exceed that of the pure δ-NbN observed in this study. © 1999 Elsevier Science S.A.
Keywords: Microhardness; Niobium; Nitride coatings; Phase composition; Titanium; Vacuum arc deposition